Nurr1: RXRα heterodimer activation as monotherapy for Parkinson’s disease - Spathis, Athanasios D.; Asvos, Xenophon; Ziavra, Despina; Karampelas, Theodoros; Topouzis, Stavros; Cournia, Zoe; Qing, Xiaobing; Alexakos, Pavlos; Smits, Lisa M.; Dalla, Christina; Rideout, Hardy J.; Schwamborn, Jens Christian; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic (DAergic) neurons in the substantia nigra and the gradual depletion of dopamine (DA). Current treatments replenish the DA deficit and improve symptoms but induce dyskinesias over time, and neuroprotective therapies are nonexistent. Here we report that Nuclear receptor-related 1 (Nurr1):Retinoid X receptor α (RXRα) activation has a double therapeutic potential for PD, offering both neuroprotective and symptomatic improvement. We designed BRF110, a unique in vivo active Nurr1:RXRα-selective lead molecule, which prevents DAergic neuron demise and striatal DAergic denervation in vivo against PD-causing toxins in a Nurr1-dependent manner. BRF110 also protects against PD-related genetic mutations in patient induced pluripotent stem cell (iPSC)-derived DAergic neurons and a genetic mouse PD model. Remarkably, besides neuroprotection, BRF110 up-regulates tyrosine hydroxylase (TH), aromatic l-amino acid decarboxylase (AADC), and GTP cyclohydrolase I (GCH1) transcription; increases striatal DA in vivo; and has symptomatic efficacy in two postneurodegeneration PD models, without inducing dyskinesias on chronic daily treatment. The combined neuroprotective and symptomatic effects of BRF110 identify Nurr1:RXRα activation as a potential monotherapeutic approach for PD.